2016
DOI: 10.1007/s11250-016-1068-8
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of mastitis and activity of milk neutrophils in Tharparkar cows reared under semi-arid conditions

Abstract: Rearing of indigenous Tharparkar (TP) cows (native of arid Thar deserts) under high humid conditions (>75 % humidity) has increased the incidence of mammary infections in them. A study was undertaken to see the number, activity, and expression of milk neutrophils isolated from healthy and mastitic cows. There was a significant (P < 0.05) influx in milk somatic cell counts (SCC) and neutrophils in sub-clinical and clinical mastitis cows. No change was observed in the phagocytic activity (PA) of milk neutrophils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 19 publications
4
19
0
Order By: Relevance
“…In addition, a positive correlation between SCC and Na content of milk was detected in the current study. These results agree with those previously observed for cows [35,36]. For example, Summer et al [35] found higher contents of Na in milk with more than 5.6021 log 10/mL than in milk with less than 5.6021 log 10/mL.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, a positive correlation between SCC and Na content of milk was detected in the current study. These results agree with those previously observed for cows [35,36]. For example, Summer et al [35] found higher contents of Na in milk with more than 5.6021 log 10/mL than in milk with less than 5.6021 log 10/mL.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we showed that MEC and the percentage of CD11b positive leukocytes increase in bacteriological positive milk samples than negative. This result agrees also with Alhussien et al [ 24 ] that observed a significant increase of MEC in cows with clinical mastitis and significant increase in mRNA expression of CD11b on isolated milk PMN from cows with sub-clinical and clinical mastitis.…”
Section: Discussionsupporting
confidence: 93%
“…There is an increase in the percentage of lymphocytes, followed by macrophages and neutrophils in normal mammary quarters [ 20 ]. However, reports of macrophage having the maximum percentage in normal milk SCC are also there [ 21 , 22 ]. Resident neutrophil in milk with low SCC might modulate the initial steps of dynamic immune defense of the udder, and percentage change in neutrophils in conjunction with SCC might provide a more reliable method for assessing the quality of milk in buffaloes [ 23 ].…”
Section: Milk Differential Leukocyte Counts (Dlcs)mentioning
confidence: 99%
“…SCC variation has been noted between various breeds of cows [ 14 , 22 , 27 , 56 - 58 ] as presented in Figure-3 . The high-producing cattle breeds such as Brown Swiss and Holstein have a higher presence of SCC/ml in milk.…”
Section: Factors Affecting Milk Sccmentioning
confidence: 99%